Renin-angiotensin system blockers and severe acute respiratory syndrome coronavirus 2 (2020)
Severe acute respiratory syndrome coronavirus 2, which is responsible for the current coronavirus disease 2019 pandemic, uses angiotensin-converting enzyme 2 as a gateway into host cells. In this review, we summarize the biology of this enzyme, which plays a key role in cardiovascular homeostasis. Blockers of the renin-angiotensin system modify the expression and activity of angiotensin-converting enzyme 2 in different ways. The effects of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers on the expression and enzyme activity of angiotensinconverting enzyme 2 are reviewed, and the consequences of these treatments for the severity of coronavirus disease 2019 infection are discussed. Abbreviations: ACE, angiotensin-converting enzyme; ACE2, angiotensin-converting enzyme 2; Ang, angiotensin; ARB: angiotensin II receptor blocker; AT1 receptor: angiotensin II receptor type 1; COVID-19: coronavirus disease 2019; RAS: renin-angiotensin system; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2.